The Influence of Product Quality and Service Quality on Customer Loyalty through Consumer Satisfaction (Study on My Caramel 1994 Jl. Pramuka Samarinda) - Sri Wahyuni; Arwin Sanjaya (Pinisi Business Administration Review, 2021)
This study aimss to determine the effecstr of product quality and service qualityy on customer loyalty through customer ssatisfaction. The type of research used is descriptive research with a quantitativee approach. The sample is 100 respondents who are customers of My Caramel 1994 Pramuka Samarinda byy using a nnon-probabilityy sample with purposive sampling techniquese and accidental sampling. Analysis of the data used is pathh analysis. The rresults showed tthat the variable product quality and servicee quality partially had a significant influence on customer ssatisfaction, the variable customer satisfaction partially had a significant eeffect on customer lloyalty, product quality and service quality variables partially did not have a significant effect onn customer loyalty, product quality andd service quality variables simultaneously have a significant eeffect on customer satisfactionn, product quality, service quality, andd customer satisfaction variables simultaneously have a significant eeffect on customerr loyalty. Thus My Caramel 1994 Pramuka Samarinda continues to strive to improve product quality and service quality. This will influence customers to be loyal through customer satisfaction.